NILAI MODERASI ISLAM DAN INTERNALISASINYA DI SEKOLAH - Ajib Hermawan (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
The growth of radical movement has been spread in education areas today, particularly in school. The growth is systematically need to be prevented. In Islamic educational context, the action that should be put is through internalization of Islamic moderation values in school. The Islamic moderation values that include tolerant, justice, balance (harmony), and equality can be fostered by education of Islamic religion (PAI) as the basic of the development. There are two important models that should be concerned with the internalization, i.e through official curriculum and hidden curriculum. Of course, the official curriculum should be the basic of the internalization, but it is not enough, it necessary to strengthen through hidden curriculum by construct the socio-cultural context that support to the transformation of Islamic moderation values in the school environment. If this process is runing well, the internalization of Islamic moderation values will reach to the optimal result and surely weaken the spread of Islamic radical movement. This article will explore and analyse the models of internalization especially on hidden curriculum in the school